Pharmacotherapy for PTSD - West, James C.; Wynn, Gary H.; Benedek, David M. (The Oxford handbook of traumatic stress disorders., 2nd ed., 2022)
Psychotropic medications offer some benefit in treatment of posttraumatic stress disorder (PTSD) symptoms. This chapter reviews classes of medications used as monotherapy and augmentation agents and evidence for their use. Antidepressant medications, particularly selective serotonin reuptake inhibitors, have the greatest body of evidence to support their use in treatment of PTSD, but the benefit they offer is modest, and they are ineffective in some populations. This chapter also reviews novel pharmacologic approaches to treatment of PTSD still under investigation. Beyond sleep, studies to date have not identified strategies to target specific symptom clusters in PTSD. Such studies may help tailor future treatment to symptoms that are either particularly disabling or refractory to other medications of psychosocial intervention. 'Repurposing' studies of older agents originally approved for other illnesses may prove effective for specific symptoms or symptom clusters of PTSD. (PsycInfo Database Record (c) 2023 APA, all rights reserved)
Keywords: Drug Therapy; PTSD; Posttraumatic Stress Disorder; medication; pharmacotherapy; posttraumatic stress disorder